The Impact of Financial Literacy and Household Food Security on the Prevention of Stunting among Toddlers in Lubuk PakamSubdistrict, Deli Serdang Regency - Br Bangun, Sri Melda; Irmayani, Irmayani; Lubis, Basyariah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Stunting is a chronic nutritional problem characterised by a child’s height being below the standard growth for their age, which impacts cognitive development, immunity, and future productivity. This study aims to analyse the influence of family financial literacy and household food security on the prevention of stunting among children under five in Lubuk Pakam District, Deli Serdang Regency, and to determine the most dominant factor. The study employed a quantitative design with a cross-sectional method. The population consisted of 130,417 families with children aged 6–59 months, with a sample of 256 respondents selected using multistage cluster sampling. Data were obtained through anthropometric measurements of children under five and questionnaires on financial literacy and food security, both of which had been validated and reliability tested. Data analysis was conducted using univariate, bivariate (chi-square test), and multivariate (logistic regression) methods. The results revealed that low financial literacy increased the risk of stunting by 2.18 times (OR = 2.18; p = 0.004), while low food security increased the risk by 3.12 times (OR = 3.12; p < 0.001). Mother’s education (p = 0.082) and family income (p = 0.162) had no significant effect. Multivariate analysis identified food security as the most dominant factor in preventing stunting, followed by financial literacy. In conclusion, strengthening household food security and improving financial literacy through education and household financial planning should be prioritised as strategies to reduce stunting prevalence among children under five.